PERANCANGAN PROGRAM PERSEDIAAN BARANG DAGANG PADA CV. SATRIA JAYA - Rifky Permana (STIKOM CKI, 2018)
ABSTRACT CV. Satria Jaya is a trade company which is engaged in sales of office stationery. Goods stock tabulation activity in CV. Satria Jaya still using manual program. With the expantion of transfer supply activity which is more rise, it is appear some problem such as some mistakes in doing the registration about transfer goods supply, less accurate report and need long time to entry data service or goods transfer report, and searching file which is need delays. Goods stock design program is a solution which is can solve the problem in this company. With this program hope can achieve goods supply entry data activity which is efficient and accurate, and getting faster information, accurate and less risk .Keywords: Program Design; Merchandise Inventory Program